Batam Immigration Officers' Perception of the Revocation of Visa-Free Visits: An Analysis in a National Security Perspective - Putra, Romil Sahab; Zahidi , M. Syaprin; Yumitro, Gonda (PERSPEKTIF, 2025)
This study analyzes the perception of Special Class I Immigration Employees of TPI Batam towards the policy of revoking the Free Visit Visa (BVK) policy for 159 countries, based on the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number M.HH-GR.01.07 of 2023. Using a qualitative approach with a non-positivist paradigm, this study explores employees' subjective interpretations of the impact of policies on national security. Data was obtained through interviews with 7 Batam Immigration employees in depth, participatory observation, and document review. With the framework of Barry Buzan's National Security Theory, the research examines elements of transnational threats, state capabilities, and collective security. The results show that the BVK revocation policy is seen as a strategic step to strengthen national security, increase PNBP, and mitigate the abuse of residence permits by foreigners. Employees consider this policy to improve the selectivity of foreigners' surveillance, which positively impacts tourism, the economy, and investment. Employee perceptions of reciprocal principles and policy benefits also support its implementation. Effective communication and common perception between employees are key factors for policy success. The research concludes that the policy of revoking BVK is relevant for national security and reflects efforts to maintain the country's stability through a collective security approach. The theoretical and practical implications are expected to guide the government in formulating a more adaptive immigration policy.